Peran Pendidikan Kewarganegaraan dalam Meningkatkan Kesadaran Wirausaha Berbasis Nilai-Nilai Kebangsaan - Wawan Shokib Rondli; Wasis Wijayanto; Nur Fajrie; Ahmad Hariyadi; Irfai Fathurohman; Oliv Via Ani Ramadhan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Citizenship education has a strategic role in forming entrepreneurial character and awareness based on national values. However, there are still challenges in integrating citizenship education with the formation of an entrepreneurial spirit oriented towards nationalism and patriotism. Therefore, this research aims to analyze how Citizenship Education can increase awareness of entrepreneurship based on national values ​​in the younger generation. This research uses qualitative research methods with a descriptive approach. Data collection was carried out through in-depth interviews, observations, and literature studies on citizenship education curricula and entrepreneurship programs in educational institutions. Data analysis was carried out using data reduction techniques, data presentation and drawing conclusions. The research results show that Citizenship Education contributes to building an entrepreneurial character who has a national spirit through strengthening values ​​such as mutual cooperation, hard work, independence and social concern. In addition, the integration of citizenship material with entrepreneurship education can raise awareness among the younger generation of the importance of contributing to national economic development through businesses based on national values. Thus, policies and innovations are needed in the education curriculum to further optimize the synergy between citizenship education and entrepreneurship.